2006
DOI: 10.1016/j.jcrysgro.2005.11.109
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD growth and electrical studies of p-type AlGaN with Al fraction 0.35

Abstract: We present a study on the high performance p-type Al x Ga 1Àx N (x ¼ 0:35) layers grown by low-pressure metalorganic chemical vapor deposition on AlN template/sapphire substrate. The influence of growth conditions on the p-type conductivity of the Al x Ga 1Àx N (x ¼ 0:35) alloy is investigated. From the Hall effect and I-V transmission line model measurements, a p-type resistivity of 3.5 O cm for Al x Ga 1Àx N (x ¼ 0:35) epilayers are achieved. To the best of our knowledge, this is the lowest resistivity ever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Carbon of 7 Â 10 17 cm À3 density was also incorporated in the N-polar sample, whereas it was incorporated below the noise level in the Al-polar. Yu et al reported nearly the same but slightly lowconcentrated profile of the oxygen incorporation as our Alpolar sample [6]. In our FM growth, Al atoms are exposed to the growth atmosphere, and this possibly concerns easier absorption of oxygen from the atmosphere.…”
Section: Article In Presssupporting
confidence: 65%
See 1 more Smart Citation
“…Carbon of 7 Â 10 17 cm À3 density was also incorporated in the N-polar sample, whereas it was incorporated below the noise level in the Al-polar. Yu et al reported nearly the same but slightly lowconcentrated profile of the oxygen incorporation as our Alpolar sample [6]. In our FM growth, Al atoms are exposed to the growth atmosphere, and this possibly concerns easier absorption of oxygen from the atmosphere.…”
Section: Article In Presssupporting
confidence: 65%
“…For deep UV light-emitting diodes (LEDs), flip-chip structures are generally needed. This is because of the quite low-conductivity of p-doped high Al-content AlGaN layers [6]. Some contact layers such as p-doped GaN layers should be grown on the p-doped AlGaN [1,2], which would be light-absorption layers.…”
Section: Introductionmentioning
confidence: 99%
“…To date, considerable effort has been expended to obtain a high hole carrier concentration. [3][4][5][6][7] Recently, we found that the activation energy of the acceptor level and the carrier concentration of the hole can be controlled by choosing a certain growth condition. In particular, if the source gases are fed in a pulse mode into a metalorganic chemical vapor deposition (MOCVD) reactor, the activation energy of the acceptor level can be drastically decreased, resulting in an increase in carrier concentration.…”
Section: Formation Of Algan and Gan Epitaxial Layer With High P-carrimentioning
confidence: 99%
“…Much effort has been expended to achieve a high concentration of hole carriers in p-AlGaN and p-GaN. [6][7][8][9][10][11][12][13] A decade ago, theorists 13 proposed the theoretical possibility of reducing the activation energy of the acceptor by means of a co-doping technique, in which pairing of two acceptors and one donor in vicinal lattice sites could reduce the energy of the acceptor level. So far, many researchers have tried to realize the reduction of the acceptor activation energy of GaN and AlGaN by the co-doping technique in which the acceptor dopant and the donor dopant were simultaneously doped into the host material of GaN and AlGaN.…”
mentioning
confidence: 99%